2019
DOI: 10.1109/tbme.2018.2879462
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Physical Modeling, Characterization, and Optimization of Electro-Quasistatic Human Body Communication

Abstract: Human Body Communication (HBC) has emerged as an alternative to radio wave communication for connecting low power, miniaturized wearable and implantable devices in, on and around the human body. HBC uses the human body as the communication channel between on-body devices. Previous studies characterizing the human body channel has reported widely varying channel response much of which has been attributed to the variation in measurement setup. This calls for the development of a unifying bio-physical model of HB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(83 citation statements)
references
References 28 publications
1
82
0
Order By: Relevance
“…Establishing a proper procedure and measurement setup for measuring IBC channel characteristics, while keeping the overall IBC signal path intact, is a very challenging task [ 156 , 157 ], since introducing any kind of measuring equipment into the IBC channel modifies the return signal path and usually influences the measurement results. The use of different measurement equipment (signal generator, oscilloscope, network and spectrum analyzer), effects caused by different cables and connections, differences when using transformers or battery powered devices, the effect of the load resistance, and ground strategies were extensively studied in [ 13 , 153 , 158 , 159 , 160 ]. It was shown that using balun transformers and commercial equipment with 50 Ω input impedance resulted in higher measured gain than in a realistic IBC channel due to the improper ground isolation, and with lower gain at low frequencies due to the low frequency termination [ 159 , 160 ].…”
Section: State Of the Art: Emerging Technologies For The Wbs Applimentioning
confidence: 99%
See 1 more Smart Citation
“…Establishing a proper procedure and measurement setup for measuring IBC channel characteristics, while keeping the overall IBC signal path intact, is a very challenging task [ 156 , 157 ], since introducing any kind of measuring equipment into the IBC channel modifies the return signal path and usually influences the measurement results. The use of different measurement equipment (signal generator, oscilloscope, network and spectrum analyzer), effects caused by different cables and connections, differences when using transformers or battery powered devices, the effect of the load resistance, and ground strategies were extensively studied in [ 13 , 153 , 158 , 159 , 160 ]. It was shown that using balun transformers and commercial equipment with 50 Ω input impedance resulted in higher measured gain than in a realistic IBC channel due to the improper ground isolation, and with lower gain at low frequencies due to the low frequency termination [ 159 , 160 ].…”
Section: State Of the Art: Emerging Technologies For The Wbs Applimentioning
confidence: 99%
“…The use of different measurement equipment (signal generator, oscilloscope, network and spectrum analyzer), effects caused by different cables and connections, differences when using transformers or battery powered devices, the effect of the load resistance, and ground strategies were extensively studied in [ 13 , 153 , 158 , 159 , 160 ]. It was shown that using balun transformers and commercial equipment with 50 Ω input impedance resulted in higher measured gain than in a realistic IBC channel due to the improper ground isolation, and with lower gain at low frequencies due to the low frequency termination [ 159 , 160 ]. Also, devices with large physical size (like commercial network and spectrum analyzers) created a larger than expected return path, whether they were isolated with baluns or not, thereby increasing the measured channel gain [ 15 , 41 , 160 , 161 , 162 , 163 ].…”
Section: State Of the Art: Emerging Technologies For The Wbs Applimentioning
confidence: 99%
“…Battery-powered devices should be used in IBC channel test. Avoid using devices with big ground, otherwise it will lead to an optimistic estimation of channel loss [29]. To avoid the common ground of the transmitter and receiver, three ways of mutually independent peripheral circuit power supply are set up: mobile power supply (portable battery), isolation transformer power supply, and uninterrupted power supply.…”
Section: F Experimental Protocolmentioning
confidence: 99%
“…When we did the human channel measurements, the power of unrelated equipment was pulled out in order to decrease the common ground interference. The power supply ways used in the experiments, which all has a small ground plane, to emulate a more realistic IBC scenario and avoid an optimistic estimation of channel loss [29]. In summary, the power supply method used in the experiment can simulate the real human communication scene.…”
Section: F Experimental Protocolmentioning
confidence: 99%
“…For practical wearable applications, channel modeling for battery-powered devices has been investigated in terms of path loss according to the frequency [40]. The previous study in [41] investigated the channel loss for important measurement issues in the HBC, in terms of ground sharing for a wearable measurement system, dependence on the excitation conditions for capacitive coupling and galvanic coupling, and impedance conditions for the measurement terminations. These works on capacitive coupling have contributed to the development of measurement setups dedicated to the human body channel and presented their unique channel properties by analyzing measured data.…”
Section: System Model a Channel Model Of Capacitive Couplingmentioning
confidence: 99%